Bone microarchitecture in patients with autoimmune hepatitis. (30th March 2021) - Schmidt, Constantin; Stürznickel, Julian; Strahl, André; Oheim, Ralf; Weiler‐Normann, Christina; Sebode, Marcial; Barvencik, Florian; Lohse, Ansgar W.; Schinke, Thorsten; Amling, Michael; Schramm, Christoph; Rolvien, Tim
ABSTRACT: In patients with autoimmune hepatitis (AIH), osteoporosis represents a common extrahepatic complication, which we recently showed by an assessment of areal bone mineral density (aBMD) via dual‐energy x‐ray absorptiometry (DXA). However, it is well established that bone quality and fracture risk does not solely depend on aBMD, but also on bone microarchitecture. It is currently not known whether AIH patients exhibit a site‐specific or compartment‐specific deterioration in the skeletal microarchitecture. In order to assess potential geometric, volumetric, and microarchitectural changes, high‐resolution peripheral quantitative computed tomography (HR‐pQCT) measurements were performed at the distal radius and distal tibia in female patients with AIH ( n  = 51) and compared to age‐matched female healthy controls ( n  = 32) as well as to female patients with AIH/primary biliary cholangitis (PBC) overlap syndrome ( n  = 25) and female patients with PBC alone (PBC, n  = 36). DXA at the lumbar spine and hip, clinical characteristics, transient elastography (FibroScan) and laboratory analyses were also included in this analysis. AIH patients showed a predominant reduction of cortical thickness (Ct.Th) in the distal radius and tibia compared to healthy controls ( p  < .0001 and p  = .003, respectively). In contrast, trabecular parameters such as bone volume fraction (BV/TV) did not differ significantly at the distal radius ( p  = .453) or tibia ( p  = .508). Linear regression models revealed significant negative associations between age and Ct.Th (95% confidence interval [CI], −14 to −5 μm/year, p  < .0001), but not between liver stiffness, cumulative prednisolone dose (even after an adjustment for age), or disease duration with bone microarchitecture. The duration of high‐dose prednisolone (≥7.5 mg) was negatively associated with trabecular thickness (Tb.Th) at the distal radius. No differences in bone microarchitecture parameters between AIH, AIH/PBC, and PBC could be detected. In conclusion, AIH patients showed a severe age‐dependent deterioration of the cortical bone microarchitecture, which is most likely the major contribution to the observed increased fracture risk in these patients. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).